Synthesis, Structure and Antioxidant Activity of Cyclohexene-Fused Selenuranes and Related Derivatives - Poonam Rajesh Prasad; Harkesh B. Singh; Ray J. Butcher (Molecules, 2015)
Synthesis, structure and antioxidant activity of new cyclohexene-fused spiroselenuranes and a spirotellurane is reported. Oxidation reactions of bis(o-formylcyclohex- 1-ene)selenide/bis(2-hydroxymethylcyclohex-1-ene)selenide provide the corresponding spiroselenuranes. The glutathione peroxidase-like activity of the newly synthesized compounds has been evaluated.